2018
DOI: 10.1002/ldr.2889
|View full text |Cite
|
Sign up to set email alerts
|

Identifying sediment source areas in a Mediterranean watershed using the SWAT model

Abstract: This study aims to evaluate the suitability of the Soil and Water Assessment Tool model in simulating runoff and sediment loss in the Carapelle (SE Italy), a typical Mediterranean watershed, where continuous measurements of streamflow and sediment concentration were collected over a 5‐year period, on a half‐hour timescale, processed on a daily timescale. After sensitivity analysis, the model was calibrated and validated for runoff and sediment. Statistics show generally satisfactory efficiency. To further impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 112 publications
(145 reference statements)
3
40
0
Order By: Relevance
“…CEA, as part of Mediterranean sub-arid catchments with low precipitation rates and accentuated water scarcity during summer, is a fragile ecosystem and some measures are needed to mitigate water resources overexploitation, as commented by other authors (Ricci et al, 2018).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…CEA, as part of Mediterranean sub-arid catchments with low precipitation rates and accentuated water scarcity during summer, is a fragile ecosystem and some measures are needed to mitigate water resources overexploitation, as commented by other authors (Ricci et al, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…Further analysis during very low flow days (measured data) is necessary (Bisantino et al, 2010;Skoulikidis et al, 2017). A calibration based on a seasonal scheme is needed (Ricci et al, 2018) and differentiated dynamic baseline flow could provide a strategy to follow (Arnold et al, 1995). Although there are some studies that report very low flows in regulated rivers in Europe (Kirkby et al, 2011), or in Spain (Martinez -Capel et al, 2011Salmoral et al, 2017), no discussion about this condition related with PBIAS is provided.…”
Section: Swat Model Sensitivity Analysis Calibration and Validationmentioning
confidence: 99%
“…Firstly, the selected model parameters affecting the discharge simulation process were inserted within SWAT-CUP calibration. Published studies of similar catchments were identified to establish initial range values plausible for the study area and Mediterranean climate conditions [2,4,58,59]. As indicated by De Girolamo and Lo Porto [30], we assumed a transposition of the groundwater parameters, soil parameters, and management parameters for the same combination of input data.…”
Section: Model Calibration and Validationmentioning
confidence: 99%
“…Apart from the effects on biotic communities, there is a growing interest in long-term hydrological dynamics in intensive-agriculture watersheds. Extensive research has shown that environmental processes governed by water flow, such as sediment loads and nitrogen and phosphorus discharges in these environments, could seriously exacerbate freshwater and groundwater pollution, salinity, and soil erosion [3][4][5][6]. The indirect effects of the modified freshwater flux and water supply associated with the local climates' uncertainties will induce changes in plant growth and the productivity of crops due to drought and heat stress [7].…”
Section: Introductionmentioning
confidence: 99%
“…The SWAT model was developed to predict the impact of land management practices on water, sediments and agricultural chemical yields in ungauged river basins [14]. The model is widely used in hydrological [8,26] and water-quality analyses at the basin scale [27,28] to assess the impact of land-use changes or climate changes on surface waters [19,29].…”
Section: Quantifying Point and Non-point Source Pollutionmentioning
confidence: 99%